Effects of Proton Pump Inhibitor Therapy for Laryngopharyngeal Reflux on Posttreatment Symptoms and Hypopharyngeal pH. (19th March 2014) - Waxman, Jonathan; Yalamanchali, Sreeya; Valle, Elizabeth Shay; Pott, Thomas; Friedman, Michael
Abstract : Objective: To determine the effect of twice‐daily proton pump inhibitor (PPI) treatment on the relationship between laryngopharyngeal pH environment and symptoms in patients with laryngopharyngeal reflux (LPR). Study Design and Setting: Retrospective analysis of records from consecutive patients seen at a single clinical site between 2009 and 2012. Subjects and Methods: Forty‐three records of patients diagnosed with LPR who underwent pre‐ and posttreatment pH studies were included. Prior to treatment, all had a Reflux Symptom Index (RSI) > 13 and an abnormal pH study. Patients were treated for ≥ 4 weeks with twice‐daily PPIs. Following treatment, patients completed a second RSI and pH study. Results: Most patients (67.4%) had symptom normalization; however, most patients (60.5%) did not have pH normalization. For all patients whose symptoms did not normalize, pH scores also did not normalize; 32.6% of patients showed no subjective or objective treatment response. For individuals whose symptoms normalized but whose pH scores did not normalize, there was a significant decrease in upright pH score. For the entire group, pretreatment symptom and upright pH scores were strongly positively correlated. Improvements in symptom and upright pH scores following treatment were moderately positively correlated. Conclusion: Laryngopharyngeal pH failed to normalize for most individuals after PPI treatment; only pH improvement was necessary for symptom normalization. Many patients had no treatment response. Laryngopharyngeal reflux patients may make up a heterogeneous group, and PPI responsivity may help explain conflicting results from previous studies. Posttreatment pH monitoring is recommended in studies investigating the efficacy of PPI therapy for LPR.